Growth and flower enhancement of Chrysanthemum indicum on inoculation with arbuscular mycorrhizae and other bioinoculants - and ANJU TANWAR, KARISHMA, ASHOK AGGARWAL* (Indian Phytopathology, 2013)
The current investigation was done under polyhouse conditions to see the effect of two dominating arbuscular mycorrhizal fungi (Funneliformis mosseae and Acaulospora laevis) along with Trichoderma viride and Pseudomonas fluorescens on growth and flowering of Chrysanthemum. All the growth parameters increased significantly after 120 days of inoculation over control. Among all the growth parameters, shoot height (66.2), number of flowers (6.3), phosphorus uptake both in shoot and root (0.05, 0.08) and total chlorophyll content (3.1) were recorded highest in triple inoculation of F. mosseae + A. laevis + T. viride while fresh and dry shoot weight (24.3, 3.3) and stomatal conductance was found highest (437.2, 41.7) in plants inoculated with dual combination of F. mosseae + T. viride. Leaf area was found maximum in single inoculation of F. mosseae (28.0). F. mosseae alone and in combination with T. viride enhanced some growth parameters but F. mosseae along with A. laevis and T. viride proved to be the best combination for growth and flowering of Chrysanthemum.